2012
DOI: 10.1111/echo.12023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Left Atrial Mechanical Function in Nondipper versus Dipper Hypertensive Patients: A Speckle Tracking Study

Abstract: Nondipping in treated hypertensive patients was associated with an adverse cardiac remodeling and impaired LA mechanical function. Further studies are warranted to demonstrate the long-term prognostic significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
5
13
0
Order By: Relevance
“…Recently, LA deformation analyses using 2D-STE proved to be superior to conventional echocardiography for detecting subtle changes in LA function. 18 In parallel with this previous study, we observed significant differences in LA strain between dippers and nondippers, although there were no differences in tissue velocity between the two groups. LA wall fibrosis is also inversely related to the strain rate and LA strain.…”
Section: Correlation Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, LA deformation analyses using 2D-STE proved to be superior to conventional echocardiography for detecting subtle changes in LA function. 18 In parallel with this previous study, we observed significant differences in LA strain between dippers and nondippers, although there were no differences in tissue velocity between the two groups. LA wall fibrosis is also inversely related to the strain rate and LA strain.…”
Section: Correlation Analysissupporting
confidence: 89%
“…patients have an increased incidence of target organ damage, 12,13 LV hypertrophy, LV diastolic dysfunction, and atrial rhythm disturbances compared with dipper patients. 18,19 Decreased LA strain is also related to atrial fibrillation. However, conventional echocardiography seems to be inadequate for detecting subclinical LA dysfunction.…”
Section: Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are confirmed in our patients who showed decreased right atrial early diastolic strain rate, and increased late diastolic strain rate. Similar findings were obtained for the left atrial mechanics in arterial hypertension [23,24].…”
Section: Right-ventricular Mechanics and Exercise Capacitysupporting
confidence: 86%
“…In untreated hypertensive patients, Tadic et al 23 found reduced two-dimensional and three-dimensional LV GLS and reduced atrial longitudinal strain in nondippers compared with dippers. Acar et al 41 also examined LA strain in dippers and nondippers and found reduced atrial function in nondippers. Others have examined right heart mechanics and found reduced function in nondippers 42.…”
Section: Discussionmentioning
confidence: 99%